DIGITAL LITERACY TRAINING FOR MSMES IN SERANG CITY TO IMPROVE SOCIAL MEDIA-BASED MARKETING - Khaeruman Khaeruman; Moh. Sutoro; Yopi Rahamdani; Salapudin Salapudin; Ihwan Satria Lesmana (Yayasan Education and Social Center, 2026)
This community service activity aims to improve the digital literacy skills of Micro, Small, and Medium Enterprises (MSMEs) in Serang City through social media-based marketing training. The activity was carried out in December 2025 using participatory training methods and direct mentoring. The activity stages included preparation, training, practice, mentoring, monitoring, and evaluation. The training materials covered digital literacy, digital marketing strategies, social media management, promotional content creation, and the use of business features on digital platforms such as Instagram, Facebook, and WhatsApp Business. The results of the activity showed an increase in participants' understanding and skills in utilizing social media as a marketing tool. Participants were able to create business accounts, create promotional content, and implement digital marketing strategies according to the characteristics of their respective businesses. In addition, the mentoring process helped participants implement digital marketing effectively and sustainably. This activity also increased participants' motivation and confidence in developing digital technology-based businesses. Thus, digital literacy training is an effective solution in helping MSMEs adapt to technological developments and increase business competitiveness in the digital era.